Biophysical Characterization of DNA Fragment Separation by Agarose Gel Electrophoresis: Quantitative Analysis of Electrophoretic Mobility : Karakterisasi Biofisik Pemisahan Fragmen DNA dengan Elektroforesis Gel Agarosa: Analisis Kuantitatif Mobilitas Elektroforesis - Zeina Salman (Academia Open, 2026)
General Background: Agarose gel electrophoresis is a fundamental technique for separating DNA fragments based on size and charge in molecular biology and biophysics. Specific Background: Quantitative characterization of DNA migration behavior provides deeper understanding of electrophoretic mobility and molecular interactions within gel matrices. Knowledge Gap: Despite established theoretical models, precise quantitative relationships between DNA fragment size, topology, and migration dynamics under controlled conditions remain insufficiently detailed. Aims: This study aims to analyze the relationship between DNA fragment size and migration velocity, determine electrophoretic mobility values, and evaluate the role of DNA topology using image-based quantification. Results: The findings demonstrate an inverse exponential relationship between fragment size and migration velocity, with smaller fragments migrating faster than larger ones. Electrophoretic mobility values ranged from 0.25×10⁻⁴ to 0.829×10⁻⁴ cm²/V·s, while structural differences between circular single-stranded DNA and linear double-stranded DNA resulted in distinct migration behaviors and frictional resistance. Novelty: The study provides quantitative validation of electrophoretic principles using digital image analysis and highlights the role of molecular conformation in migration patterns. Implications: These results offer reference data for DNA fragment analysis and support improved interpretation of electrophoretic experiments in molecular biology applications. Keywords: Gel Electrophoresis, DNA Migration, Electrophoretic Mobility, Agarose Gel, Image Analysis Key Findings Highlights Smaller fragments exhibit faster movement under constant electric field conditions Molecular conformation produces distinct separation behavior despite equal mass Digital measurement enables precise evaluation of migration parameters